Hombres violentos contra la pareja: trastornos mentales y perfiles tipológicos - Echeburúa, Enrique (2022)
The aims of this theoretical paper are to analyze the mental disorders and the most relevant psychological deficits of intimate partner violent men, as well as to identify different types of batterers according to the classifications of Holtzworth-Munroe and Stuart (1994) and of Fernandez- Montalvo and Echeburúa (1997). A review of multiple theoretical and empirical papers has been carried out with this purpose. The main results show that the aggressors usually show psychological deficits –lack of control over anger, difficulty in expressing emotions, cognitive distortions, deficit in communication skills and problem solving, and low self-esteem-, and, not as often, well-established clinical disorders (eg, alcoholism, personality disorders, delusional jealousy). In conclusion, there are different types of violent men –family only, dysphoric/borderline and generally violent/antisocial- who require treatment programs adapted to their specific characteristics and needs. Finally, the future perspectives and the most relevant goals of research are commented on.